2022
DOI: 10.3390/biology11010083
|View full text |Cite
|
Sign up to set email alerts
|

The Important Role of Sex-Related Sox Family Genes in the Sex Reversal of the Chinese Soft-Shelled Turtle (Pelodiscus sinensis)

Abstract: The Chinese soft-shelled turtle Pelodiscus sinensis shows obvious sexual dimorphism. The economic and nutrition value of male individuals are significantly higher than those of female individuals. Pseudo-females which are base to all-male breeding have been obtained by estrogen induction, while the gene function and molecular mechanism of sex reversal remain unclear in P. sinensis. Here, comparative transcriptome analyses of female, male, and pseudo-female gonads were performed, and 14,430 genes differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Chinese soft-shelled turtle P. sinensis is an important aquaculture species in China. Recent studies have demonstrated the sex dimorphism expression of SOX8 in the gonads of P. sinensis , with higher expression levels in testes [10, 11]. But the specific functional role of SOX8 in sex differentiation has not been identified in any non-mammalian vertebrates yet.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese soft-shelled turtle P. sinensis is an important aquaculture species in China. Recent studies have demonstrated the sex dimorphism expression of SOX8 in the gonads of P. sinensis , with higher expression levels in testes [10, 11]. But the specific functional role of SOX8 in sex differentiation has not been identified in any non-mammalian vertebrates yet.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese soft-shelled turtle P. sinensis is an important aquaculture species in China. Recent studies have demonstrated the sex dimorphism expression of SOX8 in the gonads of P. sinensis, with higher expression levels in testes [10,11]. But the specific functional role of SOX8 in sex differentiation has not been identified in any nonmammalian vertebrates yet.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between males and females is one of the most common phenomena in biology that occurs in behavior and morphology [ 2 ]. Some aquatic animals, such as rice field eel ( Monopterus albus ), Chinese soft-shelled turtle ( Pelodiscus sinensis ), and half-smooth tongue sole ( Cynoglossus semilaevis ), undergo sexual reversal under certain conditions, which can lead to the redifferentiation of gonads [ 3 , 4 , 5 ]. The sex reversal process involves many important components and signaling pathways, such as sex determining region Y ( SRY ), SRY-box transcription factor 9 ( SOX9 ), fibroblast growth factor 9 ( FGF9 ), and R-spondin 1 (RSPO1)/WNT/β-catenin signaling pathways [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%